EFFECTIVENESS OF USING THE PREGNANCY COMPLICATIONS MODULE MEDIA (KOMI) IN HEALTH PROMOTION FOR EARLY DETECTION OF COMPLICATIONS IN PREGNANT WOMEN IN THE TANJUNGPINANG CITY AREA - Jasda, Asmarita; Elsa Gusrianti,; Annisa Oktari Erfi, (International Journal of Social Science, 2025)
Background: More than 80 – 90 % of maternal deaths during childbirth are caused by complications during pregnancy. These complications can have an impact on the health of the mother and fetus or newborn. Seeing the many complications during pregnancy that occur, it is necessary to make efforts to reduce the incidence rate. The cause of the high maternal mortality rate may occur due to lack of exposure to information. One of the efforts to overcome pregnancy complications is by providing knowledge and health education, one of which is by using module media containing pregnancy complications (KOMI), because modules are one of the means for the public to get information. Module media can provide professional and reliable information and promotion of health services about health services, especially pregnant women with pregnancy complications. The Batu X Health Center is a health center with cases of pregnant women with pregnancy complications in Tanjungpinang city. Therefore, it is necessary to make efforts to prevent pregnancy complications, one of which is by providing information media using modules. The purpose of this community service is to increase the knowledge of pregnant women through learning using modules. The method of community service activities in the form of health promotion regarding efforts to prevent pregnancy complications by delivering material directly to pregnant women and equipped with module media. Methods: This research is a quasi-experiment with pre-posttest with control group design. The population in this study is all pregnant women with pregnancy complications with a total of 60 people divided into two groups, namely the group that gets information about pregnancy complications through social media and the group that does not get information about pregnancy complications through social media totaling 30 people per group. Data collection was carried out twice, namely pre-test and post test. The data analysis used univariate analysis to describe the characteristics of the respondents, such as maternal education and work, pregnancy history and pregnancy complications and . Each variable is calculated by means (mean), standard deviation, median and range. Before analyzing bivariate data, a data normality test was carried out. The test used was the Shapiro-Wilk test, because the number of respondents in this study was less than 50 people in each group. The parametric test used is the Independent Samples T-Test. Results : The results of the study found that the medium of the complication module (KOMI) with a p value of 0.005 was more effective for increasing knowledge with early detection of complications in pregnant women. Conclusion : There is a difference in pregnant women's knowledge about complications in pregnancy before education and after education. The average increase in knowledge after education with Module media. This module media is more effective in the implementation of Health Promotion for pregnant women regarding the early detection of complications